The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1108/prt-07-2023-0064
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study for using nano-alumina to improving mechanical properties of epoxy resin for assembling glass artifacts

Rania Abdel Gwad Eloriby,
Hamdy Mohamed Mohamed

Abstract: Purpose This study aims to assess the efficacy of nano-alumina (nano-Al2O3) in improving the performance of epoxy adhesives used to assemble archaeological glass. The conservators face a significant problem in assembling this type of artifact. Therefore, the assembling process is considered one of the important stages that must be taken care of to preserve these artifacts from damage and loss. Design/methodology/approach To evaluate the stability of adhesives, the samples were subjected to artificial aging u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The obtained results in the (CIE L*a*b*) standard color system were used to measure the color change. The following equation was used to compute the total color change (E*) on a similar spot of a similar sample both before and after cleaning [55]. ΔE=�(𝛥𝛥𝛥𝛥 * ) 2 + (𝛥𝛥𝛥𝛥 * ) 2 + (𝛥𝛥𝛥𝛥 * ) 2 The color can be described numerically in three dimensions (L* a* b*): (L*) defines lightness with a maximum value of 100 for white and a minimum of 0 for black, represents the coordinates of green (negative) and red (positive) values, and (b*) denotes the color coordinates of blue (negative) and yellow (positive).…”
Section: Measurement Of Color Changementioning
confidence: 99%
“…The obtained results in the (CIE L*a*b*) standard color system were used to measure the color change. The following equation was used to compute the total color change (E*) on a similar spot of a similar sample both before and after cleaning [55]. ΔE=�(𝛥𝛥𝛥𝛥 * ) 2 + (𝛥𝛥𝛥𝛥 * ) 2 + (𝛥𝛥𝛥𝛥 * ) 2 The color can be described numerically in three dimensions (L* a* b*): (L*) defines lightness with a maximum value of 100 for white and a minimum of 0 for black, represents the coordinates of green (negative) and red (positive) values, and (b*) denotes the color coordinates of blue (negative) and yellow (positive).…”
Section: Measurement Of Color Changementioning
confidence: 99%
“…Digital microscopy is regarded as one of the most important techniques available to restorers, and its images aid in assessing the aspects of deteriorated objects [31]. It is observed that the surface of the transparent glass bearing the paint layers is full of air bubbles (Fig.…”
Section: Digital Microscopymentioning
confidence: 99%
“…In cases where mechanical methods are insufficient, chemical cleaning solutions and solvents such as acetone and alcohol can be employed [58,59]. Next, broken pieces are carefully assembled using Kemapoxy 101 SF with 3% nano-Al 2 O 3 [31]. Afterward, any missing parts are completed, and thermal color treatments are applied.…”
Section: Proposed Conservation Stages For the Stained Glass Windowmentioning
confidence: 99%
“…However, they have been proved to be less compatible with the main wall and deteriorate faster than the wall itself, potentially causing harm to the wall paintings. [8][9][10][11][12][13] In contrast, inorganic materials are becoming increasingly popular due to their excellent compatibility and durability, [14][15][16][17] in which Ca(OH) 2 has gained the most concern. Compared with the larger micron Ca(OH) 2 particles, nanoscale Ca(OH) 2 has better permeability, larger specific surface area, and high reactivity with carbon dioxide, which can ensure the rapid carbonation of Ca(OH) 2 and obtain a higher degree of carbonation, so as to realize the effective reinforcement of cultural relics.…”
Section: Introductionmentioning
confidence: 99%